Excess mass estimates and tests for multimodality - Müller, Dietrich Werner; Sawitzki, Günther (Journal of the American Statistical Association, 1991)
We propose and study a method for analyzing the modality of a distribution. The method is based on the excess mass functional. This functional measures excessive empirical mass in comparison with multiples of uniform distribution. By the excess mass approach we separate the investigation about the number of modes from questions concerning their location. For distributions on the line, the excess mass functional can be estimated at a square-root rate. The asymptotic behavior of estimators is studied, and tests for multimodality based on the excess mass are derived.